Overlap and common correlates between depression and COPD: a narrative review - Fiammetta Iannuzzo; Francesco Nucera; Antonio Bruno; Maria Rosaria Anna Muscatello; Gaetano Caramori (Mediterranean Journal of Clinical Psychology, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by a burden of comorbid conditions, including depression, that has been related with an increased risk of exacerbations, low adherence to pharmacological treatments and behavioral interventions, and overall mortality rates. The aim of the present review was to explore the comorbidity between depression and COPD by examining epidemiological and etiopathogenetic perspectives, along with shared risk factors including the potential role of hypoxia, systemic inflammation, and drugs for COPD treatment.